Preliminary studies on hydrated cement for its reuse in geopolymers - Segura Sierpe, Yasna Pamela; Borrachero-Rosado, María Victoria; Monzó-Balbuena, José María; Payá-Bernabeu, Jordi (My University, 2016)
The carbonation of hydrated ordinary Portland cement (OPC) allows the transformation of hydrated calcium aluminates and silicates into calcium carbonate and amorphous silica/ alumina. These carbonated materials are appropriate to being used as inorganic precursors for alkaline activation. The use of sodium silicate and hydroxide solutions enables the production of cementitious gels. Two ways of carbonation of hydrated cement were studied: in a dry environment, where relative humidity did not exceed 70% and in an aqueous medium at a temperature of 5 ± 1 ° C. Both materials were micro-structurally characterised and they have been used for the manufacturing of geopolymeric mortars. These mortars reached mechanical strength between 10 and 20 MPa, depending on the activating solution, the water/binder ratio and curing time/temperature. These results show the feasibility of reusing hydrated cement contained in construction and demolition wastes.
Keywords: alkali activation; carbonation; geopolymer; hydrated cement; mechanical strength; microstructure; waste